EFEITOS DA VIBRAÇÃO NA POSIÇÃO ORTOSTÁTICA NO TRATAMENTO DE PARKINSONIANOS - FREDDI, ALINE R.; BONAMIGO, ELENITA C. B.; WEICH, FÁBIO L.; CAMPOS, MAURICIO D.; WEICH, MICHELI D.; ECKHARDT, MOACIR (Salão do Conhecimento, 2013)
Resumo